Comparative Effectiveness and Safety of Standard or Reduced Dose Dabigatran vs. Rivaroxaban in Nonvalvular Atrial Fibrillation. Issue 6 (6th February 2019) - Blin, Patrick; Dureau‐Pournin, Caroline; Cottin, Yves; Bénichou, Jacques; Mismetti, Patrick; Abouelfath, Abdelilah; Lassalle, Regis; Droz, Cécile; Moore, Nicholas
Abstract : Dabigatran and rivaroxaban at standard or reduced doses have been compared to warfarin in nonvalvular atrial fibrillation (NVAF), but not to each other. This was a new user study of standard dose and reduced dose dabigatran or rivaroxaban for NVAF in the French healthcare database, matched on gender, age, date of first dispensing, and high‐dimensional propensity score, followed 2 years. Hazard ratios (HRs; 95% confidence intervals (CI)) of stroke or systemic embolism (SSE), major bleeding (MB), or death were computed. In matched standard‐dose patients (8, 290 per arm), mean age 67 years, HRs for dabigatran vs. rivaroxaban were SSE 0.92 (95% CI = 0.67–1.26), MB 0.59 (95% CI = 0.39–0.90), and death 0.84 (95% CI = 0.65–1.11). In reduced‐dose patients (7, 639 per arm), mean age 80 years, HRs for dabigatran vs. rivaroxaban were SSE 0.73 (95% CI = 0.59–0.94), MB 0.74 (95% CI = 0.57–0.96), and death 0.95 (95% CI = 0.83–1.09). In conclusion, at either dose, dabigatran had similar or better effectiveness than rivaroxaban but lower bleeding risk. Death rates were not different.